Fostering Student Speaking Skills Through Public Speaking Engagements - Ida Ayu Oka Purnami (Universitas Pendidikan Ganesha, 2024)
Students often need help expressing opinions, articulating arguments, and actively participating in discussions. Students struggle to communicate their ideas effectively due to public speaking anxiety, uncertainty about their proficiency in the language of instruction, or inadequate preparation. This causes teachers to create learning activities to improve students' speaking skills. Based on this, this research aims to analyze the development of students' speaking skills through public speaking involvement. This research design uses a mixed methods design. This research focuses on collecting quantitative and qualitative data. The participants in this research were 38 students. Data collection methods use observation, questionnaires and tests. Data collection methods use questionnaires and tests. Data collection instruments use questionnaires and tests. The data analysis technique uses inferential statistical analysis. The results of the research are that individual presentation assignments have a very significant positive impact on students' speaking abilities. It was concluded that individual presentation assignments effectively improved students' speaking skills